Solusi Semi Analitik Persamaan Burgers Menggunakan Metode Dekomposisi Adomian Laplace - Brinda Sari; Lukita Ambarwati; Eti Dwi Wiraningsih (Program Studi Matematika Universitas Negeri Jakarta, 2023)
Burgers equation is a partial differential equation which has important rule in fluid mechanics. Because it has nonlinear terms, the exact solution is complicated to find. Therefore many methods have been developed to find the approximate solution that can estimate the exact solution. In this research, the Laplace Adomian decomposition method is applied to calculate the approximate solution of Burgers equation. The method is a semi-analytical method to resolve nonlinear differential equation. By the numerical simulation, we obtained a result that the approximate solution by this method can estimate the exact solution with the sum of absolute and relative error less than those using approximate solution obtained by the Adomian decomposition method without the use of Laplace transform. Therefore the Laplace Adomian decomposition method is more accurate than the Adomian decomposition method in order to estimate the exact solution of the Burgers equation.